Granulocyte Macrophage-Colony Stimulating Factor Produces a Splenic Subset of Monocyte-Derived Dendritic Cells That Efficiently Polarize T Helper Type 2 Cells in Response to Blood-Borne Antigen - Ryu, Seul Hye; Shin, Hyun Soo; Eum, Hye Hyeon; Park, Ji Soo; Choi, Wanho; Na, Hye Young; In, Hyunju; Kim, Tae-Gyun; Park, Sejung; Hwang, Soomin; Sohn, Moah; Kim, Eun-Do; et al. (Frontiers in Immunology, 2022)
Dendritic cells (DCs) are key antigen-presenting cells that prime naive T cells and initiate adaptive immunity. Although the genetic deficiency and transgenic overexpression of granulocyte macrophage-colony stimulating factor (GM-CSF) signaling were reported to influence the homeostasis of DCs, the in vivo development of DC subsets following injection of GM-CSF has not been analyzed in detail. Among the treatment of mice with different hematopoietic cytokines, only GM-CSF generates a distinct subset of XCR1-33D1- DCs which make up the majority of DCs in the spleen after three daily injections. These GM-CSF-induced DCs (GMiDCs) are distinguished from classical DCs (cDCs) in the spleen by their expression of CD115 and CD301b and by their superior ability to present blood-borne antigen and thus to stimulate CD4+ T cells. Unlike cDCs in the spleen, GMiDCs are exceptionally effective to polarize and expand T helper type 2 (Th2) cells and able to induce allergic sensitization in response to blood-borne antigen. Single-cell RNA sequencing analysis and adoptive cell transfer assay reveal the sequential differentiation of classical monocytes into pre-GMiDCs and GMiDCs. Interestingly, mixed bone marrow chimeric mice of Csf2rb+/+ and Csf2rb-/- demonstrate that the generation of GMiDCs necessitates the cis expression of GM-CSF receptor. Besides the spleen, GMiDCs are generated in the CCR7-independent resident DCs of the LNs and in some peripheral tissues with GM-CSF treatment. Also, small but significant numbers of GMiDCs are generated in the spleen and other tissues during chronic allergic inflammation. Collectively, our present study identifies a splenic subset of CD115hiCD301b+ GMiDCs that possess a strong capacity to promote Th2 polarization and allergic sensitization against blood-borne antigen.